Effects of selected core stabilization exercise protocol on pain and functional disability in patients with chronic non-specific low back pain - Smaeil safdari; khalil khayambashi; Gholam ali Ghasemi; Alireza Fallah; Ebahim Sekhavat (Vesnu Publications, 2014)
Introduction: low back pain is the most common musculoskeletal complication. Although there are many ways to treat low back pain, achieving a concise, simple, and compact method is required in today's industrial societies. The purpose of this study was to evaluate the effect of six weeks selected core stabilization exercises on pain and functional disability in patients with nonspecific chronic low back pain. Materials and Methods: 20 patients with nonspecific chronic low back pain (10 male, 10 women) with the average age of 24.55±3.4, average height of 164.15±9.6, and average weight of 65.25±5.04 underwent a six-week selected core stabilization exercises supervised by physiotherapist. The amount of pain and functional disability were respectively measured using VAS and ODI questionnaire both before and after the six-week exercise program. Data normality and the rate of intergroup changes were respectively calculated using Shapiro-Wilk Test and dependent student t-test (p<0.05). Also, data were analyzed using SPSS21 software. Results: results showed that, after the six-week exercise program, the amount of pain in the patients with nonspecific chronic low back pain was significantly reduced from 7.12 ± 2.13 to 3.75 ± 2.67 (p=0.00). Also, according to the results obtained from ODI questionnaire, after the six-week exercise intervention, the rate of functional disability was ameliorated significantly as it was reduced from 40.8 ± 15.42 to 23.3 ± 14.52 (p=0.00). Conclusion: according to the current study's results, the researcher's selected core stabilization exercises by reducing time of each training session, can have a significant role in rehabilitation of the patients with chronic low back pain, and make the patients use them continuously in their lifetime. Therefore, this protocol can be used as a substitute for voluminous and time consuming exercises. Keywords: core stabilization selected exercises, nonspecific chronic low back pain, functional disability, pain.